Particle tracking microrheology of cancer cells in living subjects. (October 2020) - Wu, Pei-Hsun; Gambhir, Sanjiv Sam; Hale, Christopher M.; Chen, Wei-Chiang; Wirtz, Denis; Smith, Bryan Ronain
Graphical abstract: Abstract: Cumulative evidence shows that microenvironmental conditions play a significant role in the regulation of cell functions, and how cells respond to these conditions are of central importance to regenerative medicine and cancer cell response to therapeutics. Here, we develop a new method to examine cell mechanical properties by analyzing the motion of nanoparticles in living in mice, combining particle tracking with intravital microscopy. This method directly examines the mechanical response of breast carcinoma cells and normal breast epithelial cells under intravital microenvironments. Our results show both carcinoma and normal cells display significantly reduced compliance (less deformability) in vivo compared to the same cells cultured in 2D, in both sparse and confluent conditions. While the compliance of the normal cells remains steady over time, the compliance of carcinoma cells decreases further as they form tumor-like architectures. Integrating the cancer cells into spheroids embedded in 3D collagen matrices in part redirected the mechanical response to a state closer to the in vivo setting. Overall, our study demonstrates that the microenvironment is a crucial regulator of cell mechanics and the intravital particle tracking method can provide novel insights into the role of cell mechanics in vivo .